Knowledge, Attitudes, and Practices Toward Unexplained Recurrent Pregnancy Loss Among Afflicted Women - Shi Z; Liu H; Han J; Wu X (Risk Management and Healthcare Policy)
Zuoping Shi, Huiping Liu, Jie Han, Xueqing Wu Reproductive Medicine Centre, Children’s Hospital of Shanxi and Women Health Center of Shanxi, Taiyuan, 030001, People’s Republic of ChinaCorrespondence: Zuoping Shi, Reproductive Medicine Centre, Children’s Hospital of Shanxi and Women Health Center of Shanxi, Taiyuan, 030001, People’s Republic of China, Tel +86-13934621435, Email 635328140@qq.comBackground: To explore the knowledge, attitudes, and practices (KAP) regarding recurrent pregnancy loss (RPL) of women with unexplained RPL.Methods: This cross-sectional study enrolled women with unexplained RPL in the Reproductive Medicine Centre of Shanxi Maternal and Child Health Hospital between August 28th and September 28th, 2024. Data were collected through a self-designed questionnaire encompassing sociodemographic characteristics and three dimensions of KAP.Results: A total of 485 valid questionnaires were included, with knowledge, attitude, and practice scores of 13.05 ± 6.24, 39.30 ± 3.09, and 41.11 ± 4.37, respectively. The multivariable logistic regression analysis showed that knowledge scores (OR = 1.05, 95% CI: 1.02– 1.09, P = 0.001; beneficial), attitude scores (OR = 1.30, 95% CI: 1.20– 1.41, P < 0.001), and urban residence (OR = 0.64, 95% CI: 0.41– 0.99, P = 0.049) were independently associated with the proactive practice. The structural equation modeling (SEM) showed that knowledge directly (β = 0.20, P = 0.001) and indirectly (β = 0.15, P < 0.001) influenced practices.Conclusion: Women with unexplained RPL demonstrated insufficient knowledge, moderate attitude, and proactive practice towards RPL. Targeted educational interventions could be needed to enhance knowledge related to RPL, which may help women form proper expectations toward pregnancy.Keywords: knowledge, attitude, practice, recurrent pregnancy loss, cross-sectional study